2017
DOI: 10.25125/engineering-journal-ijoer-may-2017-4
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction and Testing of a Hybrid Photovoltaic (PV) Solar Dryer

Abstract: The thin layer drying behaviour of tomato slices using a hybrid drying method compared to solar and open sun drying was investigated. The dryer consists of solar collector, photovoltaic solar panel, battery and drying chamber. The dryer was operated as both a solar-energy dryer and as a hybrid solar dryer. The drying performance of the dryer was evaluated with fresh tomato slice and compared with open sun drying under the same climatic conditions. The dryer recorded a raised temperature of 62℃ attainable in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…However, due to dust, dirt, fungi, bacteria, and animal attacks, the product may be spoiled as studied in [4]. The controlled drying system involves the use of active and passive solar dryers as described in [5]. Thus, the active solar dryer is an efficient solar dryer used in small firms for drying products for a brief time period, but the technology is still expensive for farmers as discussed in [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to dust, dirt, fungi, bacteria, and animal attacks, the product may be spoiled as studied in [4]. The controlled drying system involves the use of active and passive solar dryers as described in [5]. Thus, the active solar dryer is an efficient solar dryer used in small firms for drying products for a brief time period, but the technology is still expensive for farmers as discussed in [6].…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid solar dryer with solar panels and electrical resistances [21], was also used to dehydrate the moisture content of mushrooms. A comparison of drying methods between direct drying under the sun and hybrid solar dryer was explored by [22], to dry tomato slices in Nigeria. The study's conclusion revealed that the use of hybrid solar-energy dryer using photovoltaic gives a promising result and more superior in tomato preservation than OSD.…”
Section: Solar Pvmentioning
confidence: 99%
“…This method of drying is still widely used nowadays. However, open sun drying faces many inherent limitations like overexposure to the sun, which causes food damage, high losses in yield production due to insects, rodents, and birds, longer drying time, and unpredictable climate conditions [1] [2] [3]. With such disadvantages, solar dryers' implementation has drawn promising effects, especially of high-valued crops [4].…”
Section: Introductionmentioning
confidence: 99%
“…The collector efficiency was 45% and useful heat of 48.9 W m-2 K -1 was used for about 6 h in drying during the night. Hussein et al (2017) research on the design, construction and test of a hybrid photovoltaic solar dryer showed that, it took 6 h to reduce the moisture content of tomato slices from the initial value of 94.22% to the final value of 10% (w.b.). This is different to the 9 h it took to achieve same moisture content when solar dryer was used.…”
Section: Solar Drying Research In Nigeriamentioning
confidence: 99%